2004
DOI: 10.1002/app.20593
|View full text |Cite
|
Sign up to set email alerts
|

Combination of bifunctional aldehydes and poly(vinyl alcohol) as the crosslinking systems to improve paper wet strength

Abstract: Two bifunctional aldehydes (i.e., glyoxal and glutaraldehyde) are used as the crosslinking agents to improve paper wet strength in the presence of fully hydrolyzed poly(vinyl alcohol) (PVA) as a co-reactant. These bifunctional aldehydes alone improve paper wet strength but diminish its folding endurance. The use of PVA as a coreactant not only improves paper wet strength but also increases its dry strength and folding endurance. Glutaraldehyde is able to impart much higher levels of wet strength to the treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 6 publications
1
25
0
Order By: Relevance
“…Several authors investigated the crosslinking potential of cellulose with glutaraldehyde. Xu et al [12] reported the use of glutaraldehyde and glyoxal to impart higher levels of wet strength to paper, comparing their different reactivities with cellulose. Choi et al [13] tested the use of these two aldehydes for replacement of formaldehyde in durable press finishing of cotton, reporting higher efficiency of glutaradehyde in the crosslinking with cellulose.…”
mentioning
confidence: 99%
“…Several authors investigated the crosslinking potential of cellulose with glutaraldehyde. Xu et al [12] reported the use of glutaraldehyde and glyoxal to impart higher levels of wet strength to paper, comparing their different reactivities with cellulose. Choi et al [13] tested the use of these two aldehydes for replacement of formaldehyde in durable press finishing of cotton, reporting higher efficiency of glutaradehyde in the crosslinking with cellulose.…”
mentioning
confidence: 99%
“…Dipping the sheets in different solutions improved the wet strength of the handsheets, but the treated handsheets became more brittle, especially when the crosslinking system combining glyoxal and chitosan was employed. The reduction of folding endurance is possibly a result of crosslinking between pulp fibers, which limits the mobility of cellulose molecules and thus reduces the flexibility of paper sheets (Xu et al 2004). The dry strength indices of all the treated handsheets were lower than that of the control sample (96.1 Nmg -1 ).…”
Section: Folding Endurance and Dry Strength Of Treated Handsheetsmentioning
confidence: 93%
“…Glyoxal is reported as a crosslinking agent to improve the wet strength of paper in a dipping process that can provide temporary wet strength to paper without the aid of a catalyst and improve the permanent wet strength to some extent when catalysts such as Zn(NO 3 ) 2 are used (Xu et al 2002). Compared with glyoxal alone, the combination of glyoxal and polyvinyl alcohol (PVA) as a crosslinking system can achieve higher folding endurance when the wet strength of paper is improved (Xu et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…1 compare to no. 2), since fines and small fiber fragments in between the long fibers cause more fiber joints in the network, which increased the strength properties (Xu et al 2004;Horvath et al 2010). At higher magnification, the fiber joints of the UV-radiated reference sample (Fig.…”
Section: Tga Measurementsmentioning
confidence: 99%
“…Crosslinking of cellulose has been shown to increase the wet strength properties of paper because of stronger fiber-fiber joints in the fiber network (Xu et al 2004;Horvath et al 2010). Crosslinking or grafting of cellulose can be performed in different conditions, such as plasma treatment (Zubaidi and Hirotsu 1996), irradiation Chen and Wang 2006;Kumar et al 2006), ionic grafting (Ikeda et al 1988;Tsubokawa et al 2000), and ring-opening reactions (Toledano-Thompson et al 2005).…”
Section: Introductionmentioning
confidence: 99%